Inspiration Mr. Blackwell schedule - Unidentified author (Colorado State University. Libraries, 2000)
Syllabus for the Inspiration Mr. Blackwell special summer course taught by Dr. Eulanda Sanders and Curator Linda Carlson in 2000.
Keywords: Fashion -- History; Fashion -- Exhibitions